INOVASI PEMANFAATAN SAYURAN MENJADI SMOOTHIE DAN ICE CREAM SAYUR - Widayanti, Nila; Maimurni, Santa; Mulyadi, Dita Sari; Ratnasari, Noviana Dwi Putri; Aisyah, Siti; Syahria, Nukmatus (LPPM Universitas PGRI Adi Buana Surabaya, 2018)
Vegetable is a way of traditional treatment of ancestral heritage that has long been known in Indonesia. Vegetable as a culture of the Indonesian Society desperately needs to be preserved. In an effort to preserve herbs and improve the benefits of herbal medicine in Indonesia, the Division of Work Program